How mindfulness shapes AI competence: a structural equation modeling analysis of mindfulness, AI literacy and behavioral intention in Chinese media students - Lan, Yanling; Liu, Sihang; Xia, Linjie (Frontiers in Psychology, 2025)
IntroductionArtificial Intelligence (AI) literacy, defined as the knowledge and ability to recognize, apply, and evaluate AI, is a key driving force of digital transformation and technological innovation. In the media industry, the demand for “intelligent+” interdisciplinary talent has prompted universities to embed AI literacy training into talent development programs. While curriculum systems have been progressively refined, the challenge remains on how to activate students’ intention to embrace and effectively utilize AI. Mindfulness, a metacognitive trait that enhances cognitive flexibility, self-regulation, and creativity, may contribute to the development of AI literacy, although its specific impact in this progress remains largely unexplored.MethodsThis study constructs the integrated model of “Mindfulness-AI Literacy-Technology Application“. Survey data were collected from 588 media students in China and analyzed using SPSS and SmartPLS to conduct structural equation modeling. AI literacy is comprised of four dimensions: acknowledgment of AI (AAI), AI ethics (AIE), AI collaboration (AIC), and AI self-efficacy (AIS).ResultsMindfulness significantly and positively influenced AAI, AIE, and AIC, but showed no significant relationship with AIS. It also had a significant direct positive effect on AIBI. Furthermore, AAI and AIC partially mediated the relationship between mindfulness and AIBI.DiscussionResults confirm that mindfulness is an effective internal pathway for strengthening key AI literacy dimensions and enhancing media students’ intention to apply AI technologies. Incorporating mindfulness interventions into higher media education, aligned with curriculum and practice, could provide a strategic approach to cultivating AI-ready graduates.